Strategi Public Relation Melalui Pemanfaatan Instagram Sebagai Media Promosi pada â€œDakon Restoâ€ Banyuwangi Jawa Timur - Pertiwi, Ratih; Ariyani, Nafiah (International Journal of Demos (IJD), 2023)
AbstractToday's social media seems to be an idol star in modern society. The closeness of an individual and social media are two things that cannot be separated. This provides an opportunity for the business sector, especially the culinary sector, to take advantage of social media as a means of market opportunities. there is a need for a combination of public relations in providing various indications and broad public relations effects. Public relations works most effectively when integrated into the areas of product quality, customer service, and corporate identity. Hence the element of credibility that builds a platform for publicity. Through the use of social media (Instagram) Dakon Resto hopes to achieve a goal, namely as an effective way in a public relations strategy where Instagram is used as a promotional medium to attract the performance and quality of the restaurant. This study uses a qualitative method with a phenomenological approach. So as to conclude, Dakon Resto's social media (Instagram) has an important role in planning a public relations strategy as a promotional medium, for example when online newsrooms become effective when inviting visitors to browse through social media sites (Instagram) to obtain more in-depth information.Keywords: Strategy, Public Relations, Instagram, Media Promotion, Dakon RestoÂ AbstrakMedia sosial saat ini seolah menjadi bintang idola di tengah masyarakat modern. Kedekatan seorang individu dan media sosial merupakan dua hal yang tidak dapat dipisahkan. Hal ini, memberikan peluang bagi sektor bisnis khususnya bidang kuliner untuk memanfaatkan media sosial sebagai sarana dari peluang pasar tersebut. Sehingga diperlukan adanya perpaduan public relation dalam memberikan indikasi yang beragam dan efek public relation yang luas. Public relation bekerja secara efektif jika diintegrasikan ke dalam area kualitas produk, pelayanan pelanggan, dan identitas perusahaan. Maka elemen kredibilitas yang membangun platform untuk publisitas. Melalui penggunaan media sosial (Instagram) Dakon Resto berharap menghasilkan tujuan yakni sebagai cara yang efektif dalam strategi public relation yang mana instagram sebagai media promosi untuk menarik performa dan kualitas restoran tersebut. Penelitian ini menggunakan metode kualitatif dengan pendekatan secara fenomenologi. Sehingga menghasilkan kesimpulan, media sosial (Instagram) Dakon Resto memiliki peranan penting dalam merencanakan strategi public relation sebagai media promosi salah satu contohnya saat ruang redaksi online menjadi efektif ketika mengundang pengunjung untuk menelusuri melalui situsÂ  media sosial (Instagram) untuk memperoleh informasi lebih mendalam.Kata Kunci: Strategi, Public Relation, Instagram, Media Promosi, Dakon Resto